2009
DOI: 10.1007/s10856-009-3828-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hydroxyl groups on Ca adsorption on rutile surfaces: a first-principles study

Abstract: Hydroxyl groups on titanium surfaces have been believed to play an important role in absorbing Ca in solution, which is crucial in the formation of bioactive calcium phosphates both in vitro and in vivo. CASTEP, a first-principles density functional theory (DFT) code, was employed to investigate Ca adsorption on various rutile (110) surfaces in order to clarify how hydroxyl groups effect Ca adsorption. The surfaces modeled in the present study include a bare rutile (110) surface, a hydroxylated rutile (110) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Ti surface seemed to be more abundant, which might be attributed to the formation of the anatase phase after heat treatment at 500 • C. Previous studies have shown that only weakly absorbed OH − disappears at lower heat-treatment temperatures, while OH − that is strongly bounded with Ti remains on the surface at temperatures up to 600 • C and more [30,31]. Moreover, it has been observed that only strongly bounded OH − groups are responsible for the bioactivity of Ti surfaces [32,33].…”
Section: Discussionmentioning
confidence: 95%
“…Ti surface seemed to be more abundant, which might be attributed to the formation of the anatase phase after heat treatment at 500 • C. Previous studies have shown that only weakly absorbed OH − disappears at lower heat-treatment temperatures, while OH − that is strongly bounded with Ti remains on the surface at temperatures up to 600 • C and more [30,31]. Moreover, it has been observed that only strongly bounded OH − groups are responsible for the bioactivity of Ti surfaces [32,33].…”
Section: Discussionmentioning
confidence: 95%
“…The deprotonation of Ti-OH to Ti-Osurface groups due to the lower isoelectric point (iep) of TiO2 compared to the pH of body fluids (iepTiO2 = 5-6, physiological pH = 7.4) favours the electrostatic attraction of calcium ions. 8,9 This has been shown to lead to the formation of metastable calcium phosphate which can be transformed to bone-like hydroxyapatite during bone remodelling. 10,11 Further, Ti-OH surface groups play an important role in the interaction with biomolecules, particularly for the adsorption of serum proteins such as albumin and fibronectin.…”
Section: Titanium and Titanium Dioxide In Biomedical Applicationsmentioning
confidence: 99%
“…Moreover it has been observed that only strongly bound hydroxyls groups are effectively responsible of titanium bioactivity [40,43].…”
Section: Hydroxyls Expositionmentioning
confidence: 99%